2011
DOI: 10.1039/c1ob05114h
|View full text |Cite
|
Sign up to set email alerts
|

A pH-responsive carboxylic β-1,3-glucan polysaccharide for complexation with polymeric guests

Abstract: The helix-forming nature of β-1,3-glucan polysaccharides is a characteristic that has potential for producing gene carriers, bio-nanomaterials and other chiral nanowires. Herein, carboxylic curdlan (CurCOOH) bearing the β-1,3-polyglucuronic acid structure was successfully prepared from β-1,3-glucan polysaccharide curdlan (Cur) by one-step oxidation using a 4-acetamido-TEMPO/NaClO/NaClO(2) system as the oxidant. The resulting high-molecular-weight CurCOOH was proved to bear the 6-COOH group in 100% purity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 76 publications
(19 reference statements)
2
19
0
Order By: Relevance
“…Upon addition of CurCOOH to a solution of complex 1 , a significant decrease in the absorption at approximately 275 nm was found, with a concomitant growth of a low‐energy absorption shoulder centered at 550 nm (Figure 1 a). Given that CurCOOH does not absorb in the visible region,27a the absorption spectral changes cannot be accounted for by the intrinsic UV/Vis absorption of the newly added CurCOOH. The p K a value of CurCOOH has been reported to be 3.11,27a therefore the carboxylic acid groups on CurCOOH should undergo deprotonation, and hence CurCOOH would likely exist as a polyanion in the pH 6.8 buffer solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon addition of CurCOOH to a solution of complex 1 , a significant decrease in the absorption at approximately 275 nm was found, with a concomitant growth of a low‐energy absorption shoulder centered at 550 nm (Figure 1 a). Given that CurCOOH does not absorb in the visible region,27a the absorption spectral changes cannot be accounted for by the intrinsic UV/Vis absorption of the newly added CurCOOH. The p K a value of CurCOOH has been reported to be 3.11,27a therefore the carboxylic acid groups on CurCOOH should undergo deprotonation, and hence CurCOOH would likely exist as a polyanion in the pH 6.8 buffer solution.…”
Section: Resultsmentioning
confidence: 99%
“…Given that CurCOOH does not absorb in the visible region,27a the absorption spectral changes cannot be accounted for by the intrinsic UV/Vis absorption of the newly added CurCOOH. The p K a value of CurCOOH has been reported to be 3.11,27a therefore the carboxylic acid groups on CurCOOH should undergo deprotonation, and hence CurCOOH would likely exist as a polyanion in the pH 6.8 buffer solution. As a result, the cationic complex 1 molecules would probably form helical assemblies with the anionic CurCOO − in the pH 6.8 buffer solution through electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the material shows potential in the production of gene carriers, bio-nanomaterials, and other chiral nanowires through hydrogen bonding interactions, hydrophobic interactions, and electrostatic attraction. 49 Thus, a possible mechanism underlying the rheological behavior of the carboxylic curdlan is proposed in Fig. 6.…”
Section: 48mentioning
confidence: 99%
“…34 Recently, pH-responsive carboxylic b-1,3-glucan polysaccharide was used to selectively complex single-walled carbon nanotubes and PT1s in aqueous solution. 35 More interestingly, natural polypeptides are also pH-responsive systems with helical structures. In 2010, Cho et al 36 reported the synthesis of a basic oligopeptide, Api 8 , composed of eight non-natural achiral amino acids.…”
Section: Solvent-mediated Transformationmentioning
confidence: 99%